Studi Kekasaran Permukaan Hasil Proses Milling CNC Agma A-8 Pada Material Baja Karbon Sedang Menggunakan Mata Pahat HSS 3 Flute (Jurnal Teknik Mesin Unsyiah, 2021)
Quality Surface roughness is very influential in the process of making the product made. The purpose of the study was to test the surface roughness of the milling process of the CNC Agma A-8 machine. In this study using a CNC agma A-8 machine. The cutting tool was used endmill HSS 3 flute with a diameter of 10 mm, medium carbon steel material with a length of 100 mm and a width of 50 mm, a surface roughness test tool Mitutoyo SURFTEST SJ-310. Variations of parameters used are feed speed 71.55 mm/min, 95.4 mm/min, 119 mm/min, 143 mm/min, and for depth of cut 0.5 mm, 1 mm, 1.5 mm, 2 mm. The measurement results show a surface value of 1.005 m at a feeding speed of 71.55 mm/min at a depth of cut of 0.5 mm while at a roughness level of 5.003 m at a feeding speed of 143 mm/min and a depth of cut of 2 mm. It can be concluded that the depth of cut and feeding speed affect the surface roughness value, which is included in the roughness class N6 to N8.